Sediment Properties and Seagrass Density Influence the Morphological Plasticity of Seagrass Zostera muelleri More Than Elevated Temperatures - Daniel S. Swadling; Skye L. Taylor; Renee K. Gruber; Tim M. Glasby (Estuaries and Coasts, 2025)
Understanding the long-term effects of elevated temperatures on foundational species like seagrasses is critical for predicting and managing the impacts of warming coastal ecosystems worldwide. Seagrasses exhibit plasticity in response to a range of environmental stressors, so the effects of climate change are likely to be context dependent. This study investigated differences in the growth and morphology of Zostera muelleri inside versus outside a warm water plume generated by a power station operating for ~ 26 years in Lake Macquarie, New South Wales, Australia. The effects of other factors, including sediment organic matter, season and seagrass density were also examined to ascertain their importance relative to elevated temperatures. Despite water temperatures in the thermal plume being equivalent to conditions predicted by 2090 under future climate scenarios (1.5–2.7 °C above ambient), there were no consistent effects of these elevated temperatures on Z. muelleri growth and morphology. Instead, growth at all sites (ambient and warm water) was greater by 40.3% in spring and 74.3% in summer when compared to winter. Increasing organic matter content in sediments was associated with a 69.8% rise in below-ground biomass and a subsequent 73.8% reduction in the ratio of above- to below-ground biomass. There was also evidence for seagrass density effects, with denser meadows having shorter leaves and reduced growth rates, likely due to self-shading. Overall, these findings demonstrate that Z. muelleri in the centre of its distribution in eastern Australia can tolerate moderate temperature increases over decadal scales.